Business communication building critical skills - Locker, Kitty O.; Kaczmarek, Stephen Kyo (McGraw-Hill/Irwin, 2011)
Enhances students knowledge of marketing management and to advance their skills in developing successful marketing strategies. This book focuses on the six stage learning approach.